2010
DOI: 10.1080/15235882.2010.502797
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Bilinguals Over Monolinguals in Learning a Third Language

Abstract: The present study is an examination of the contribution of bilingualism to trilingualism, namely the influence of learning two different orthographies on learning a third. The participants were two groups of sixth graders from Israeli schools who were studying English as a foreign (second or third) language: Russian Israeli children for whom Russian was their native language and Hebrew was their second language and a control group of native Hebrew speakers. The participants were administered cognitive and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 67 publications
2
39
1
Order By: Relevance
“…Their findings indicated that speech perception and phonological awareness are important predictors for reading in English among both students groups. Similar findings were revealed regarding phonological awareness transfer in language pairs German-English (Mann & Wimmer, 2002), Dutch-English (Timmer & Schiller, 2012;Morfidi et al, 2007), Farsi-English (Arab-Moghaddam & Sénéchal, 2001;Gholamain & Geva, 1999), Finnish-English (Dufva & Voeten, 1999), French-English (Comeau, Cormier, Grandmaison, & Lacroix, 1999;Chiang & Rvachew, 2007), Italian-English (D'angiulli et al, 2001), Portuguese-English (da Fontoura & Siegel, 1995), and Russian-English (Abu-Rabia, 2001;Abu-Rabia & Sanitsky, 2010). The findings of all of these studies support Cummins's IH (1979, 1981.…”
Section: Phonological Awarenesssupporting
confidence: 58%
“…Their findings indicated that speech perception and phonological awareness are important predictors for reading in English among both students groups. Similar findings were revealed regarding phonological awareness transfer in language pairs German-English (Mann & Wimmer, 2002), Dutch-English (Timmer & Schiller, 2012;Morfidi et al, 2007), Farsi-English (Arab-Moghaddam & Sénéchal, 2001;Gholamain & Geva, 1999), Finnish-English (Dufva & Voeten, 1999), French-English (Comeau, Cormier, Grandmaison, & Lacroix, 1999;Chiang & Rvachew, 2007), Italian-English (D'angiulli et al, 2001), Portuguese-English (da Fontoura & Siegel, 1995), and Russian-English (Abu-Rabia, 2001;Abu-Rabia & Sanitsky, 2010). The findings of all of these studies support Cummins's IH (1979, 1981.…”
Section: Phonological Awarenesssupporting
confidence: 58%
“…In this study, we define decoding as a process during which a reader converts letters (graphemes) to sounds (phonemes) and, essentially, to language. When assessing decoding, researchers often measure how accurately (e.g., Abu‐Rabia & Sanitsky, ; Nassaji & Geva, ) or efficiently (i.e., fast and accurately; e.g., Jeon, ) readers read real and/or pseudowords. Because accuracy and efficiency scores are often interchangeably used as an index of decoding ability by L2 reading researchers, it is not uncommon for meta‐analysts to treat both accuracy and efficiency measures as representing decoding (Melby‐Lervåg & Lervåg, ; Melby‐Lervåg et al., ), and the present study also follows this approach.…”
Section: Background To the Meta‐analysismentioning
confidence: 99%
“…Although certain subconstructs of phonological awareness operate across languages (see Branum‐Martin et al., ), our review of the literature revealed that, at least within L2 reading research, it is more often tested by a language‐specific instrument (e.g., an English phonological awareness test for English reading comprehension research). More specifically, some popular test tasks involve phonemic manipulation such as phonemic deletion, substitution, or blending (Abu‐Rabia & Sanitsky, ; Kieffer & Lesaux, ; Pasquarella, Chen, Lam, Luo, & Ramirez, ). The present study, therefore, reports the average correlation between such measures of L2 phonological awareness and L2 reading comprehension.…”
Section: Background To the Meta‐analysismentioning
confidence: 99%
“…An alternate, more positive explanation is that participants who reported having studied more than one language showed little change in their implicit beliefs based on the successful laboratory learning experience precisely because they have more experience with languages, which in itself has been shown to be a positive contributing factor to subsequent language (specifically script) acquisition (e.g., Abu-Rabia and Sanitsky, 2010).…”
Section: Considerations For Future Researchmentioning
confidence: 99%